The Call to Perfection, financial Asceticism, and Jerome - Dunn, Geoffrey D. (Augustinianum, 2012)
The encounter between Jesus and the rich young man in Mt. 19,16-30 (with parallels in Mc. 10,17-31 and Lc. 18,18-30) provides the setting for the teaching on the attaining of perfection, which is presented as a three-step process: the selling of one’s possessions, the distribution of the proceeds to the poor, and the following of Christ (Mt. 19,21; Mc. 10,21; Lc. 18,22; and the unique Lukan saying in 12,33). It was a passage to which Jerome appealed frequently in his writings and which Finn, in his recent monograph, believes demonstrates Jerome’s extreme views. In this paper I shall examine Jerome’s references to this biblical passage in his letters and treatises to evaluate whether the first two steps in the process (self-dispossession and almsgiving) were considered equally virtuous by Jerome.